Chapter Philological Remarks on the Sealings from Empire Period of Karkemish - Peker, Hasan (Studia Asiana, 2023)
Over 500 clay sealings from the Hittite Empire Period were retrieved in a LB II stratum of Area C East in the Lower Palace area (excavations seasons 2017-2021). 301 clay sealings were sealed 493 times by over 50 different seals belonging to c. 35 officials. In this paper, philological comments will be made about the officials of the relevant archive whose names and/or titles/professions are legible and a new interpretation of the sign L254 will be suggested as an Addendum.